2011
DOI: 10.1111/j.1440-172x.2011.01933.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' knowledge of prevention and management of pressure ulcer at a Health Insurance Hospital in Alexandria

Abstract: Nurses' knowledge of pressure ulcer prediction, prevention and management plays a very important role in the incidence and prevalence of pressure ulcers in health-care systems. The aim of the current study was to assess the nurse's knowledge about prevention and management of pressure ulcer at one of the largest health insurance hospitals in Alexandria. A descriptive cross-sectional study using an interview questionnaire format to assess the nurses' knowledge (n = 122) regarding prevention of pressure ulcers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 20 publications
8
36
1
5
Order By: Relevance
“…The current findings also indicated that, while receiving training on PU prevention affects attitudes towards PUP, reading research articles on the topic does not. This is supported by several previous studies, [15,17,30] but also contradicted by Aslan and Yavuz van Giersbergen. [12] This difference may be explained by the type of training received by the nurses in our study compared to other studies; while nurses usually undergo more traditional training, interactive learning is needed if we need to improve attitudes.…”
Section: Discussionsupporting
confidence: 84%
“…The current findings also indicated that, while receiving training on PU prevention affects attitudes towards PUP, reading research articles on the topic does not. This is supported by several previous studies, [15,17,30] but also contradicted by Aslan and Yavuz van Giersbergen. [12] This difference may be explained by the type of training received by the nurses in our study compared to other studies; while nurses usually undergo more traditional training, interactive learning is needed if we need to improve attitudes.…”
Section: Discussionsupporting
confidence: 84%
“…Found the significance of this study is a nurse's knowledge were significantly higher when exposed to educational material. In Egypt, study by El Enein & Zaghloul, [39] who using a descriptive crosssectional study with 122 subjects. This study demonstrated that, unless a nurse had received pressure ulcer education within the past year, his/her knowledge was below the minimal acceptable standards.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the study in Germany by Meesterberends et al (2013) (33) , who found that the knowledge among nurses employed in Dutch hospitals about the usefulness of preventive measures is moderate, another study done in Bulgaria by Beeckman et al (2010) (34) found inadequate knowledge on prevention of PU, though knowledge was not correlated with application of preventive measures attitude between nursing records of the skin condition with actual skin examination in relation to PU. In the Arab world, Abou-Elenin &Zaghloul (2011) (35) , in Egypt reported that 70% of nurses scored useful measures in PU care and 66% of them scored nonuseful measures were in use in PU care. (36) investigated knowledge level of intensive care unit nurses regarding pressure ulceration and therefore the impact of the education program on the level of knowledge and found that nurses' level of knowledge was good before receiving education.…”
Section: Discussionmentioning
confidence: 99%